Evaluating Customer Perceptions and Their Influence on Organizational Branding in the Hotel Industry: A Strategic Perspective (Journal of Informatics Education and Research, 2025)
India is a country with ‘unity in diversity’ which favours the hotels and hospitality sector. The changing nature of the hospitality sector emphasizes how important consumer perceptions are becoming in determining corporate branding tactics. The important relationship between customer perceptions and hotel organizations’ brand identities is examined in this study, with a focus on how customer satisfaction, service quality, and brand associations all work together to affect brand equity. The study examines important factors like ambience, responsiveness, personalization, and dependability from a strategic standpoint in order to determine how these aspects of service experience affect customer loyalty and the development of brand perception. Using a structured questionnaire and statistical tools, primary data was gathered from hotel patrons of strategically placed hotel chains throughout India's Golden Quadrilateral in order to investigate the relationships and causes. The results show that favourable consumer perceptions greatly increase trust and brand recognition, both of which support long-term competitive advantage. Additionally, the study finds discrepancies between customer expectations and service delivery, providing branding managers with useful information to refocus their tactics on experience-centric models. Hotels can build long-term brand equity and improve customer relations by closing the service-performance gap. By highlighting the critical role that customer-centric practices play in fostering organisational success and brand differentiation in the highly competitive hotel industry, this study adds to the body of research on strategic branding.